Cytogenetic analysis reveals swamp status of the indigenous ‘Bhangor’ buffalo population from Tripura - SINGH, KARAN VEER; DAS, RAMENDRA; NIRANJAN, SAKET; KATARIA, R S (The Indian Journal of Animal Sciences, 2022)
The domestic water buffalo (Bubalus bubalis) isclassified into the swamp and riverine. However, theirhybrids are also found in some parts of Assam (BrahmaputraValley) in North-east India. Swamp buffaloes have a typicalphenotypic appearance, like the shape of horns, small bodysize as compared to riverine breeds, and body-colour, etc.This study characterizes the indigenous non-descript‘Bhangor’ buffalo population from the Tripura state usingkaryotype analyses. Blood samples were collected fromunrelated animals of both sexes phenotypically identifiedas swamp buffaloes from the breeding tract in Unakotidistrict which has >50% of indigenous buffalo populationin Tripura. The blood leukocytes were cultured, terminated,and harvested using conventional karyotype protocol asstandardised in lab to determine the number ofchromosomes present in the metaphase chromosomespreads after 72 h incubation at 37°C with intermittentshaking in the incubator. Chromosomal spread showedpresence of 2N=48 chromosomes, comprised of 23 pairsof autosomes and a pair of sex chromosomes with clearlydistinct size of fourth pair of metacentric chromosome. Andfor the first time, non-descript indigenous buffalo population‘Bhangor’ from Tripura has been characterized usingkaryotypic analysis.